Geometric Modeling of the Nasal Valve - Sclafani, Anthony P.; Victor, Wasnard; Sclafani, Matthew S. (Facial Plastic Surgery, 2017)
We have used a simple geometric model to examine forces affecting the nasal valve after dorsal reduction and spreader graft placement. The study was designed on the geometric modeling of the internal nasal valve (INV). Published measurements of the leptorrhine nose were used to construct a geometric model of the INV. The changes in the cross-sectional area (CSA) occurring after reduction rhinoplasty were calculated algebraically, as was the effect of these changes on the tendency of the lateral wall of the INV to collapse. The effect of spreader grafting on the CSA was determined, and the total change in CSA of the INV in various scenarios was determined and compared with the reported normal CSA. Relative to published norms, the gain in CSA from spreader grafting can be significant if thick grafts are used. When the lateral wall of the INV is conceptualized as a cantilevered beam fixed medially, the reduction of length reduction of the lateral segment of the INV can significantly reduce the tendency for the inward collapse of the lateral wall. The reduction in CSA of the INV associated with dorsal nasal reduction can be ameliorated through the placement of spreader grafts. Moreover, the reduction in length of the INV sidewall also limits inward collapse, assuming it is firmly reattached to the dorsal septum. An enhanced appreciation of the physical properties of the INV anticipated through a simplified geometric analysis will be invaluable to the rhinological surgeon interested in enhancing nasal function.
Keywords: internal nasal valve; rhinoplasty; spreader graft; upper lateral cartilage